1993
DOI: 10.3354/meps097299
|View full text |Cite
|
Sign up to set email alerts
|

Fate of particle-bound bacteria ingested by Calanus pacificus

Abstract: Bacteria bound to particles can be ingested by marine calanoid copepods, thus potentially providing a direct trophic link between bacteria and metazoa provided the microbes are digested by the animals. If some bacteria survive gut passage, they might play a role in fecal pellet solubilization and fragmentation (via ectoenzymes) and decomposition. We examined whether Calanus pacificus could assimilate bacterial biomass and whether a significant fraction of the ingested bacteria passed into the fecal pellets ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 18 publications
1
34
2
1
Order By: Relevance
“…The concentration of bacteria associated with faecal pellets was generally higher than the concentration on the amorphous aggregates (Table 2) and was in the same range as those found in laboratory-produced faecal pellets from zooplankton fed on bacterized food (10' to 10tO ml-l). This may be due to the rapid growth of a significant fraction of bacteria which survive gut passage (Lawrence et al 1993). These investigators also found that a high proportion of aminopeptidase activity was carried out by bacteria in the faecal pellets and proposed that they may be important in faecal pellet solubilization and degradation.…”
Section: Flux Of Attached Bacteria and Cyanobacteria Into The Deep Oceanmentioning
confidence: 82%
See 1 more Smart Citation
“…The concentration of bacteria associated with faecal pellets was generally higher than the concentration on the amorphous aggregates (Table 2) and was in the same range as those found in laboratory-produced faecal pellets from zooplankton fed on bacterized food (10' to 10tO ml-l). This may be due to the rapid growth of a significant fraction of bacteria which survive gut passage (Lawrence et al 1993). These investigators also found that a high proportion of aminopeptidase activity was carried out by bacteria in the faecal pellets and proposed that they may be important in faecal pellet solubilization and degradation.…”
Section: Flux Of Attached Bacteria and Cyanobacteria Into The Deep Oceanmentioning
confidence: 82%
“…They may be a food-chain short cut whereby material normally too small for organisms higher in the food chain can be ingested (Lampitt et al 1993a). Cyanobacteria can survive the passage through zooplankton and nekton guts (Johnson et al 1982, Lampitt et al 1993a) while around 30% of attached bacteria may be assimilated (Lawrence et al 1993). The ability of cyanobacteria to survive gut passage are reflected in the concentrations found in faecal pellets (Table 2b) …”
Section: Microbiology Of Ne Atlantic Aggregatesmentioning
confidence: 99%
“…However, the significance of zooplankton association goes beyond pathogenic bacteria, because zooplankton harbors very diverse bacterial phylotypes (19) in great abundances. For example, a single zooplankter can harbor up to 10 9 bacteria (27,28), which is equivalent to or higher than ambient bacterial concentrations. With 10 zooplankters·L −1 , not uncommon for lakes during the growth season (29), up to 10 10 bacteria/L could be associated with the animals.…”
Section: Resultsmentioning
confidence: 99%
“…8; but these may be overestimates, as discussed). Depending on the size of the particles to which bacteria were attached, this bacterial production could be directly available to a variety of detritivores (Lawrence et al 1993, Crump & Baross 1996. Such transfer of bacterial product~on to the higher trophic levels is probably quite important because of the direct nature of the transfer.…”
Section: Discussionmentioning
confidence: 99%